Structural, electrical and optical properties of (K, Ba)(Nb, Ni)O3–δ electroceramics: Oxygen vacancy and grain size effects. Issue 12 (15th August 2020) - Guerra, J.D.S.; Silva, M.C.O.; Silva, A.C.; Oliveira, M.A.; Mendez-González, Y.; Monte, A.F.G.; M'Peko, J.-C.; Hernandes, A.C.
Abstract: KNbO3 -based ferroelectric materials have been largely investigated as a result of many interesting physical properties that make them suitable for designing multifunctional electronic components. In particular, ferroelectric (1– x )KNbO3 – x BaNi1/2 Nb1/2 O3–δ (KBNN) solid solutions have received special attention for optical applications, including for high-performance photovoltaic devices. In this work, KBNN ceramics were produced via conventional solid-state sintering, followed by a comprehensive study of their (micro)structural, electrical and optical properties. The processed data are analyzed and discussed in terms of the effect from structural oxygen-vacancy defects in such materials and from the grain size, in the specific case of the observed electrical response. Overall, the results suggest these perovskite-structured semiconducting ferroelectric oxides as a good alternative for solar cell applications.